625.COMPARATIVE EFFICIENCY ANALYSIS FOR THE DEVELOPED MODELS - Igor, Trifunovski; Gligorce, Vrtanoski (MECHANICAL ENGINEERING – SCIENTIFIC JOURNAL, 2021)
Efficiency is a measure for delivery of the selected goals with minimum use of the existing resources. The researches in the paper are focused on analyzing the quality and efficiency of the products developed, with special emphasis on their use in the renewable resources area. The developed products are mathematical models of systems for producing thermal energy using collectors for sanitary hot water and generation of electricity using photovoltaic panels. The f-Chart method and the PVGIS software were both used in the implementation and development of the mathematical models. The quantitative parameters obtained from the mathematical models developed for both systems show the segments of use and the opportunities for savings and improvements. When cross-references, they can be used to calculate coefficients of quantitative and qualitative indicators, which are then used for comparative analysis of the quality and efficiency of the developed models. The comparative analysis of the specific qualitative indicators shows that the system using collectors for sanitary hot water has far better use of the solar radiation, the annual thermal energy expressed in financial units on annual basis is much greater compared to electricity generated using photovoltaic panel system.